emigrations of Prophet Ibrahim Khalil (peace be upon him) in the Holy Quran and the Torah - Jasim, Dr.Jawad Kazem (Thi Qar Arts Journal, 2023)
The migration of the prophets in the Holy Quran and the Torah holds significant and extensive importance in the movement of history because they had a great and direct influence on history throughout the ages. Through their numerous migrations, they played an important and influential role in the course of human civilization. Migration, like social matters, can be for good or for evil. A person may migrate to achieve legitimate or illegitimate goals, or for immediate or temporary interests. One may migrate for a noble purpose such as preserving religion or guiding people, which is emphasized by multiple Quranic verses. The study of the migrations of the Prophet Abraham as a model to the places he migrated to for the purpose of spreading his heavenly message is important, despite the scarcity of information about the migrations of the prophets and the lack of ancient historical studies specialized in archaeology concerning the reports about the migrations of the prophets. These studies often rely on narrative reports, some of which are tainted with myths and Israelite stories, and include forgeries of some historical facts.